Repeat what after whom? Exploring variable selectivity in a cross-dialectal shadowing task - Walker, Abby; Campbell-Kibler, Kathryn (Frontiers in Psychology, 2015)
Twenty women from Christchurch, New Zealand and sixteen from Columbus Ohio (dialect region U.S. Midland) participated in a bimodal lexical naming task where they repeated monosyllabic words after four speakers from four regional dialects: New Zealand, Australia, U.S. Inland North and U.S. Midland. The resulting utterances were acoustically analyzed, and presented to listeners on Amazon Mechanical Turk in an AXB task. Convergence is observed, but differs depending on the dialect of the speaker, the dialect of the model, the particular word class being shadowed, and the order in which dialects are presented to participants. We argue that these patterns are generally consistent with findings that convergence is promoted by a large phonetic distance between shadower and model (Babel, 2010, contra Kim, Horton & Bradlow, 2011), and greater existing variability in a vowel class (Babel, 2012). The results also suggest that more comparisons of accommodation towards different dialects are warranted, and that the investigation of the socio-indexical meaning of speciﬁc linguistic forms in context is a promising avenue for understanding variable selectivity in convergence.